Differential Altered Auditory Event‐Related Potential Responses in Young Boys on the Autism Spectrum With and Without Disproportionate Megalencephaly. Issue 8 (3rd June 2019) - De Meo‐Monteil, Rosanna; Nordahl, Christine Wu; Amaral, David G.; Rogers, Sally J.; Harootonian, Sevan K.; Martin, Joshua; Rivera, Susan M.; Saron, Clifford D.
Abstract : Autism spectrum disorder (ASD), characterized by impairments in social communication and repetitive behaviors, often includes altered responses to sensory inputs as part of its phenotype. The neurobiological basis for altered sensory processing is not well understood. The UC Davis Medical Investigation of Neurodevelopmental Disorders Institute Autism Phenome Project is a longitudinal, multidisciplinary study of young children with ASD and age‐matched typically developing (TD) controls. Previous analyses of the magnetic resonance imaging data from this cohort have shown that ∼15% of boys with ASD have disproportionate megalencephaly (DM) or brain size to height ratio, that is 1.5 standard deviations above the TD mean. Here, we investigated electrophysiological responses to auditory stimuli of increasing intensity (50–80 dB) in young toddlers (27–48 months old). Analyses included data from 36 age‐matched boys, of which 24 were diagnosed with ASD (12 with and 12 without DM; ASD‐DM and ASD‐N) and 12 TD controls. We found that the two ASD subgroups differed in their electrophysiological response patterns to sounds of increasing intensity. At early latencies (55–115 ms), ASD‐N does not show a loudness‐dependent response like TD and ASD‐DM, but tends to group intensities by soft vs. loud sounds, suggesting differences in sensory sensitivity in this group. At later latencies (145–195 ms), only the ASD‐DM group shows significantly higher amplitudes for loud sounds. Because no similar effects were found in ASD‐N and TD groups, this may be related to their altered neuroanatomy. These results contribute to the effort to delineate ASD subgroups and further characterize physiological responses associated with observable phenotypes. Autism Res 2019, 12: 1236–1250 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay summary: Approximately 15% of boys with ASD have much bigger brains when compared to individuals with typical development. By recording brain waves (electroencephalography) we compared how autistic children, with or without big brains, react to sounds compared to typically developing controls. We found that brain responses in the big‐brained group are different from the two other groups, suggesting that they represent a specific autism subgroup.